Evaluating the success of treatments that slow spread of an invasive insect pest. Issue 10 (19th June 2021) - Walter, Jonathan A; Rodenberg, Clare A; Stovall, Atticus E L; Nunez‐Mir, Gabriela C; Onufrieva, Ksenia S; Johnson, Derek M
Abstract: BACKGROUND: Treatments for the suppression and eradication of insect populations undergo substantial testing to ascertain their efficacy and safety, but the generally limited spatial and temporal scope of such studies limit knowledge of how contextual factors encountered in operational contexts shape the relative success of pest management treatments. These contextual factors potentially include ecological characteristics of the treated area, or the timing of treatments relative to pest phenology and weather events. We used an extensive database on over 1000 treatments of nascent populations of Lymantria dispar (L.) (gypsy moth) to examine how place‐based and time‐varying conditions shape the success of management treatments. RESULTS: We found treatment success to vary across states and years, and to be highest in small treatment blocks that are isolated from other populations. In addition, treatment success tended to be lower in treatment blocks with open forest canopies, possibly owing to challenges of effectively distributing treatments in these areas. CONCLUSIONS: Our findings emphasize the importance of monitoring for early detection of nascent gypsy moth colonies in order to successfully slow the spread of the invasion. Additionally, operations research should address best practices for effectively treating with patchy and open forest canopies. © 2021 Society of Chemical Industry. Abstract : Treatment success for invading Lymantria dispar populations varies spatiotemporally, with greatest success in small treatment blocks that are isolated from established populations and have continuous forest cover.